Strategy To Increase Religious and Moral Values In Early Childhood - Nisa, Khoirun; Al Hasyimi, Muhammad Luthvi; Mardhiyah, Ulfa Ainul (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
This research examines strategies for increasing religious and moral values ​​in early childhood through literature study. The focus of the research is to identify and analyze various strategies that are effective in instilling religious and moral values ​​in children aged 0-8 years. The research results show several main strategies that are effective, namely habituation in daily life, example from adults, storytelling and storytelling methods, project-based learning and direct experience, and educational games. Habituation and example have proven to be the most effective in terms of success in shaping children's moral behavior. Collaboration between educational institutions and parents is a key factor in optimizing the implementation of this strategy. Continuous evaluation is needed to monitor the child's moral development and the effectiveness of the strategies implemented.